The Impact of Information System Design Quality on E-Learning Systems Performance - Altarawneh, Haroon; Tarawneh, Mohammad Mahmoud (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Advanced technology-based educational practices have emerged as a constructive growth trend in the sustainable educational market. As a result, using informational communication practices in a developed market has resulted in better communicative approaches during the global pandemic situation. Creating engaging content in the educational process empirically ensured the student engagement level. This research aims to identify the impact of information systems on quality emergence aspects in e-Learning system performance. Furthermore, understanding the scope of the education process using e-Learning systems, identifying the impact of information systems on quality design in the e-Learning platform, and evaluating the advantages and disadvantages of the e-Learning platform. The Technology Acceptance Model (TAM) has been used for quality assurance and sustainable growth development in educational practices. Advanced information system design with proper monitoring approaches has improved the situation. A model is proposed to illustrate the relationship between information systems design and e-learning performance. The higher the level of quality in information system design, the higher the level of performance of the e-learning system, and thus the higher the degree of learning quality output.